The chimerical and multifaceted marine acoel Symsagittifera roscoffensis: from photosymbiosis to brain regeneration - Bailly, Xavier; Laguerre, Laurent; Correc, Gaëlle; Dupont, Sam; Kurth, Thomas; Pfannkuchen, Anja; Entzeroth, Rolf; Probert, Ian; Vinogradov, Serge; Lechauve, Christophe; Garet-Delmas, Marie-José; Reichert, Heinrich; et al. (Frontiers in Microbiology, 2014)
A remarkable example of biological engineering is the capability of some marine animals to take advantage of photosynthesis by hosting symbiotic algae. This capacity, referred to as photosymbiosis, is based on structural and functional complexes that involve two distantly unrelated organisms. These stable photosymbiotic associations between metazoans and photosynthetic protists play fundamental roles in marine ecology as exemplified by reef communities and their vulnerability to global changes threats. Here we introduce a photosymbiotic tidal acoel flatworm, Symsagittifera roscoffensis, and its obligatory green algal photosymbiont, Tetraselmis convolutae (Lack of the algal partner invariably results in acoel lethality emphasizing the mandatory nature of the photosymbiotic algae for the animal’s survival.) Together they form a composite photosymbiotic unit, which can be reared in controlled conditions that provide easy access to key life-cycle events ranging from early embryogenesis through the induction of photosymbiosis in aposymbiotic juveniles to the emergence of a functional “solar-powered” mature stage. Since it is possible to grow both algae and host under precisely controlled culture conditions, it is now possible to design a range of new experimental protocols that address the mechanisms and evolution of photosymbiosis. S. roscoffensis thus represents an emerging model system with experimental advantages that complement those of other photosymbiotic species, in particular corals. The basal taxonomic position of S. roscoffensis (and acoels in general) also makes it a relevant model for evolutionary studies of development, stem cell biology and regeneration. Finally, it’s autotrophic lifestyle and lack of calcification make S. roscoffensis a favorable system to study the role of symbiosis in the response of marine organisms to climate change (e.g. ocean warming and acidification). In this article we summarize the state of knowledge of the biology of S. rosc